Synthesis and characterization of waste polyethylene/Bi2O3 composites reinforced with CuO/ZnO nanoparticles as sustainable radiation shielding materials - Awad, Eman H.; Raslan, Heba A.; Abou‐Laila, M. T.; Taha, Eman O.; Atta, M. M. (Polymer engineering and science, 2024)
In the present research, waste polyethylene (WPE)/Bi2O3 composites have been investigated as lightweight, inexpensive, and nontoxic lead‐free γ‐ray shielding materials. Different WPE‐based composites were prepared with varying concentrations of Bi2O3 (30 and 40 phr). The effect of adding ZnO and CuO nanoparticles (NPs) inside the WPE/Bi2O3 (30) matrix was studied by incorporating 10 phr of NPs inside it. The nanocomposites' structural, thermal, and mechanical properties and competence in shielding against γ‐radiation are studied. The outcomes revealed that the mechanical properties of the pristine WPE were enhanced after incorporating Bi2O3 by 30 phr, and then it worsened after increasing the Bi2O3 ratio to 40 phr. In contrast, better mechanical properties were obtained for those composites with NPs, where the maximum tensile strength (16.2 MPa) was recorded for the WPE/Bi2O3/CuO composite (higher than WPE by 47.27%). Numbers of parameters like μm, HVL (half‐value layer), TVL (tenth value layer), RPE%, and percentage of heaviness can denote the efficiency of shielding properties of composites at 662 KeV from 137Cs point source. It was found that μm and RPE% reach the maximum value for WPE/Bi2O3 (40 phr). Adding NPs decreases μm of WPE/Bi2O3 (30) slightly. Highlights Composites based on waste polyethylene (WPE)/Bi2O3 (30 and 40 phr) were fabricated. Nano CuO and ZnO improved the mechanical properties of WPE/Bi2O3 (30). WPE/Bi2O3 (40) composites show the best shielding characteristics. Nano CuO and ZnO slightly decreased μm of WPE/Bi2O3 (30). Synthesis and characterization of waste polyethylene (WPE) and different WPE/Bi2O3 nanocomposites for radiation shielding applications.